Into the deep: the functionality of mesopelagic excursions by an oceanic apex predator. Issue 15 (28th June 2016) - Howey, Lucy A.; Tolentino, Emily R.; Papastamatiou, Yannis P.; Brooks, Edward J.; Abercrombie, Debra L.; Watanabe, Yuuki Y.; Williams, Sean; Brooks, Annabelle; Chapman, Demian D.; Jordan, Lance K.B.
Abstract: Comprehension of ecological processes in marine animals requires information regarding dynamic vertical habitat use. While many pelagic predators primarily associate with epipelagic waters, some species routinely dive beyond the deep scattering layer. Actuation for exploiting these aphotic habitats remains largely unknown. Recent telemetry data from oceanic whitetip sharks ( Carcharhinus longimanus ) in the Atlantic show a strong association with warm waters (>20°C) less than 200 m. Yet, individuals regularly exhibit excursions into the meso‐ and bathypelagic zone. In order to examine deep‐diving behavior in oceanic whitetip sharks, we physically recovered 16 pop‐up satellite archival tags and analyzed the high‐resolution depth and temperature data. Diving behavior was evaluated in the context of plausible functional behavior hypotheses including interactive behaviors, energy conservation, thermoregulation, navigation, and foraging. Mesopelagic excursions ( n = 610) occurred throughout the entire migratory circuit in all individuals, with no indication of site specificity. Six depth‐versus‐time descent and ascent profiles were identified. Descent profile shapes showed little association with examined environmental variables. Contrastingly, ascent profile shapes were related to environmental factors and appear to represent unique behavioral responses to abiotic conditions present at the dive apex. However, environmental conditions may not be the sole factors influencing ascents, as ascent mode may be linked to intentional behaviors. While dive functionality remains unconfirmed, our study suggests that mesopelagic excursions relate to active foraging behavior or navigation. Dive timing, prey constituents, and dive shape support foraging as the most viable hypothesis for mesopelagic excursions, indicating that the oceanic whitetip shark may regularly survey extreme environments (deep depths, low temperatures) as a foraging strategy. At the apex of these deep‐water excursions, sharks exhibit a variable behavioral response, perhaps, indicating the presence or absence of prey. Abstract : Although often regarded as the consummate predator, sharks face a life‐long challenge to locate and capture prey. Using a theoretical approach and the most current biotelemetry instruments, we show that even the oceans' apex predators regularly survey extreme environments (deep depths, low temperatures) as a foraging strategy. At the apex of these deep‐water excursions, sharks exhibit a variable behavioral response for the return to more hospitable surface waters, perhaps, indicating the presence or absence of prey.